Instruments reliability to measure the skill development to prevent leprosy in postgraduate studies - Tania Alemán Martínez; Onesio Esteban de León Gutiérrez; Daniela María Hernández Alemán (Medisur)
Foundation: the specific skills of the profession are oriented to the professional mode of action through the application of the clinical and epidemiological method that allows diagnosing, treating, rehabilitating, promoting health and preventing diseases. Objective: to evaluate the reliability of two instruments that measures the skill development level to prevent leprosy. Methods: a descriptive-cross-sectional study was carried out from January to May 2024, at the Julio Castillo Teaching Polyclinic, in Chambas, Ciego de Ávila, Cuba. Two measurement instruments are proposed, a survey and an observation guide, to determine the skill development level to prevent leprosy. The reliability and internal consistency of the instruments were estimated using Cronbach's alpha coefficient. The universe was 36 residents in Comprehensive General Medicine. Results: For the survey, Cronbach's alpha was 0.898 and question eight had the highest standard deviation (0.586) with respect to the mean. For the observation guide, Cronbach's alpha was 0.888 and item seven had the highest standard deviation (0.791). In both instruments, the Cronbach's alpha coefficient when an element is removed does not show significant changes that suggest eliminating or reformulating items. Conclusions: The degree of reliability obtained with the application of both instruments guarantees the correlation between the items they evaluate and shows reliability in the data, so both instruments are reliable to evaluate the ability development level to prevent leprosy.